Mammal Richness and Diversity in Tropical Ecosystem: The Role of Protected Area in Conserving Vertebrate Fauna, Oban Hill’s Region (2020)
Documenting the diversity and distribution of vertebrates is crucial to achieving sustainability and assists in planning for the protection and conservation strategy. We conducted a line transect via stratified distance sampling techniques to estimate the densities and diversity of forest mammal in tropical ecosystem landscape of Oban Hills Region, Cross River Park National (CRNP), Nigeria. A detection function was estimated individually for each land use types by pooling all the animal data from the transects. For fauna species, all sighting records of the two out of four land use types (core and buffer) were used because both accounted for the high significant percentage 36% core and 30% buffer of the species composition encountered in the land use types respectively. In total, core, buffer, farmfallow and plantation recorded 868, 519, 136, and 48 individuals respectively. Their individual density was estimated at 69.8km2, 64.8km2, 25.7km2 and 8.3km2 for all the land use types respectively. Core of the park accounted for the highest fauna species richness (D=4.138) and plantation recorded the least of (D=2.583). Analysis of Fauna species evenness and species diversity revealed that, farm fallow had the highest values (J´= 0.7536) and (H’= 2.55) respectively. The density in our study area are among the highest in the tropical rainforest. Our results indicate that Oban hills habour highest diversity of fauna in the region and also gives an updated account of fauna composition present in the region. Our finding conclude that core of the park is of the highest conservation value and priority should be given for its protection. The study also provides baseline data for future managing and planning of vertebrate population in the Oban region. We recommend that a biomonitoring study of mammals be initiated to help determine population trends, update species status in this biodiversity hotspot.